Flash annealing yields a strong and ductile medium Mn steel with heterogeneous microstructure. (June 2021) - Wan, Xinhao; Liu, Geng; Yang, Zhigang; Chen, Hao
Abstract: Austenite reversion treatment (ART) is usually used to obtain retained austenite (RA) in medium Mn steel (MMS). In this contribution, we proposed a flash-annealing strategy to produce MMS, which allows us to efficiently obtain a large amount of RA in MMS via the "explosive" nucleation of austenite and the fast C partitioning. Furthermore, flash-annealing can also render a heterogeneous ferritic matrix consisting of recrystallized/non-recrystallized ferrite grains, leading to heterogeneous deformation-induced hardening. As compared to the conventional ART processed MMS, the unique heterogeneous microstructure in the flash-annealed MMS leads to a higher yield and ultimate tensile strength but a marginal ductility loss. Flash-annealing provides an alternative route to tailor microstructure and optimize the mechanical performance of steels. Graphical abstract: Image, graphical abstract